(untitled) (Medico Legal Update, 2021)
Otitis media bacterial infections during childhood may contribute to the development of repeated nasopharyngeal infections and it is complicated of recurrent or chronic middle ear diseases, especially with multidrug resistant strains. The results of antibiotic synergism for the most prevalent three bacterial species, isolated from otitis media infections in children, and had the highest antibiotic resistance was revealed that combinations ceftazidimeamikacin and ceftazidime- ciprofloxacin displayed synergistic activity fractional inhibitory concentration (FIC ? 0.5) against the most of tested isolates; Pseudomonas aeruginosa, Porteus mirabilis, and Klebsiella pneumonia. In the biofilm test all tested isolates were showed biofilm production by tissue culture plate method (TCP), in the present study, the strong biofilm production was most prevalent in Pseudomonas aeruginosa (100%) followed by S. aureus (71.4%). Biofilm formation increases the activity of antibiotics in children otitis media infections and using antibiotics combinations may be essential for optimum management of OM patients.